Geological Science and the Making of Colonial Oil Frontiers on the East Coast of Sumatra, 1890-1930 - Harnawan, Tedy (Universitas Gadjah Mada, 2023)
In the early 20th century, the Dutch Empire emerged as a prominent oil producer internationally, with the Netherlands East Indies leading the way in petroleum production. The colonial petroleum industry’s success was bolstered by scientific and technological advancements that streamlined the oil exploitation process. Geology played a critical role as a scientific tool that facilitated the conquest of landscapes and crude oil control along Sumatra’s east coast. The study of geology supported the colonial oil politics, leading to a new era of oil mining exploitation through robust economic partnerships between the Dutch colonial government and private oil companies. This paper aims to explore the link between Dutch colonial scientific agency and the establishment of an oil extraction territory that transformed the natural environment and social conditions on the east coast of Sumatra, from Aceh to Palembang.